al-‘Alāqah al-Irtibāṭīyah bayn al-Bī’ah al-Lughawīyah wa-Mahārāt al-Lughah al-‘Arabīyah ladá Ṭalabat al-Ma‘had - Mubarak, Aniz Faizatul; Putra, Wahyu Hanafi; Salma, Kunti Nadiyah (Al-Ma‘rifah, 2022)
This research stems from environmental problems at Arrisalah Islamic International College (Pondok Modern Arrisalah Program International), Gundik, Slahung, Ponorogo, East Java, in creating a language environment that is thought to have something to do with proficiency in Arabic language skills. This study aims to describe the relationship between the language environment and the language skills possessed by students. The type of research used in this study is quantitative with correlational methods. The data collection techniques used observation, interviews, and tests on 59 people. The results of this study indicate that the relationship between them is powerful and is shown by the correlation coefficient calculation that the significance value of the correlation t count (0.810) is greater than the indication value of the correlation t table (0.250). These results indicate that the alternative hypothesis (Ha) proposed is accepted and the null hypothesis (Ho) is rejected, which means a significant relationship exists between the two variables.